THE FUNCTIONING OF THE MUSIC INDUSTRY IN CONTEMPORARY UKRAINE: FROM CONCERT TO COPYRIGHT - Parkhomenko, Iryna (Ukrainian Cultural Studies, 2023)
The relevance of the research lies in the need to determine the fundamental principles of the functioning of the music industry in contemporary Ukraine, as reflected in its policies and legislation, as Ukrainian artists continue to actively create music products despite the ongoing armed conflict. Artists in Ukraine require transparent mechanisms for generating their own income, based on a coordinated system of legislation. The article explores the fundamental principles of the functioning of the music industry in contemporary Ukraine, as reflected in Ukraine’s cultural policy and legislation, through an analysis of cultural policies regarding music and concert activities of artists in various periods of the Soviet Union, and by comparing it with the current reality in the Ukrainian music market. The study used a systemic and dialectical approach, as well as methods of analysis, synthesis, description, and comparison. The terminological basis of Ukrainian cultural legislation pertaining to the functioning of the music industry and market is analyzed. The absence of terms designating activities related to the production of commercial music products is identified, despite the fact that the music market continues to operate even in times of martial law. An analysis of the fundamental principles of the USSR’s cultural policy regarding music in different periods is conducted, and the main state authorities responsible for controlling the concert activities of artists are identified. In the conclusions, it is emphasized that the roots of the fundamental principles of today’s cultural policy in the field of music and concert activities in Ukraine still lie in the narrative of concert activities, as it was in the Soviet Union, but without ideological component. Although there are established norms of copyright legislation that allow for progress towards protecting the rights of Ukrainian artists. Further research can focus on studying the path to the popularity of a musical performer in the Soviet Union and comparing it with the situation in Ukraine: from independence to the present day.